Correlation between self-perceived cognitive problems and objective cognitive impairment in non-CNS cancer patients in a resource-constrained health setting in South Africa - Antonio G. Lentoor; Tiro B. Motsamai (Exploration of Neuroscience)
Aim: Cognitive complaints are frequent among cancer patients. These issues can significantly affect the patient’s quality of life and are linked to a higher risk of developing dementia. However, their occurrence does not consistently correlate with measurable objective cognitive dysfunction, which contributes to their negligence in oncological care. Thus, this study aimed to examine the relationship between subjective and objective measures of cognitive function in patients without CNS involvement in a developing context. Methods: A cross-sectional study was conducted with 50 patients aged 18 and above shortly after diagnosis of non-CNS cancer but before any systematic treatment at a tertiary hospital in Gauteng. The patients completed a self-perceived cognitive impairment (PCI) assessment, and the mini-Montreal Cognitive Assessment (mini-MoCA) as an objective measure of cognition. Correlational analyses were conducted to examine the relationship between self-perceived cognitive problems and performance on the mini-MoCA. Results: The results of the study revealed the presence of both self-perceived cognitive problems and objective cognitive impairments among the study cohort. There was a small non-significant association between self-PCI and the objective measure of cognitive impairment on the mini-MoCA, rs(43) = 0.220, P = 0.147. Notably, only the memory sub-domain showed a significant but moderate positive association with self-PCI, rs(43) = 0.325, P = 0.029. Conclusions: This study offers initial evidence of both subjective and objective cognitive impairment in non-CNS cancer patients before treatment in a resource-constrained setting. While there was a small non-significant association between global objective cognitive impairment and patients’ PCIs, a significant moderate association was revealed between the memory sub-domain and PCI. These results underscore the need for thorough cognitive assessment before treatment, as both the presence of cognitive impairment and patients’ perceptions of it can influence treatment compliance and everyday functioning.